Keabsahan Sertipikat Sebagai Alat Bukti yang terbit karena Pendaftaran Sistematis Lengkap (PTSL) dalam Prespektif Peraturan Pemerintah Nomor 24 Tahun 1997 tentang Pendaftaran Tanah - Heni Rizanah (LAW Proscientist: Journal of Law Profesional Scientist, 2022)
The Agrarian Reform, which the proclaimer echoes, has yet to be felt equally by the Indonesian people due to overlapping regulations regarding land registration issues. The government, as a tool to legitimize land rights for all Indonesian citizens, has not been able to create a coordinated system without overlapping in making policy rules regarding land registration. By using normative juridical legal research methods as well as statutory approaches, conceptual approaches, and historical approaches will describe the validity of certificates issued from complete systematic land registration in terms of the perspective of Government Regulation Number 24 of 1997. The government through the minister of agrarian and spatial planning / head of the national land agency should be able to carry out the mandate of the 1945 constitution, Article 33 concerning land rights as best as possible through simple, fast and definite legal provisions or regulations in order to realize a just and fair agrarian reform. equitable distribution of land for all Indonesian people.